Avaliação do banco de sementes do solo como indicador de recuperação em sistemas agroflorestais - Melo, Ualas Marques (Universidade Federal de São Carlos, 2023)
The use of seed banks has been widely used in ecological recovery projects around the world. The soil seed bank includes all viable seeds present in the soil or litter. To evaluate the composition of soil seed banks as an indicator of recovery in agroforestry systems. 128 samples were collected, 64 soil samples and 64 litter samples. The collection and storage of the seed bank considered the number of individuals. The arboreal survey considered quantity and diversity. The results of the analyzes made it possible to understand the interactions and adaptation of species to the environment, taking into account that all the information obtained is valuable and will serve as strategies for the conservation and management of SAFs. Information that may contribute to soil recovery in the future. In addition, it contributes to sustainable agricultural practices and the better management of these systems. Analysis of seed banks revealed that agroforestry systems play an important role in conserving biodiversity. It was possible to see that initially the herbs will colonize in the seed bank. However, seed bank analysis is just an evaluation tool and needs to be combined with other recovery practices. To better understand the seed bank as an indicator of recovery in SAFs, research will be needed to thoroughly study the composition of the bank.
Assessment of the soil seed bank as an indicator of recovery in agroforestry systems
Keywords: Agroecossistemas; Agroecologia; Sustentabilidade; Agroecosystems; Agroecology; Sustainability; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL; CIENCIAS AGRARIAS